Estudio de la prevalencia de la Hematuria Vesical Enzoótica Bovina en la parroquia Palanda del cantón Palanda de la provincia de Zamora Chinchipe - Cueva Zumba, Diómedes Paul (2015)
These research “Study of the prevalence of bovine enzootic hematuria Bladder Palanda Parish in Canton Palanda of the Province of Zamora Chinchipe” 96 animal samples were analyzed by three methods: Clinical Diagnostics, Urine test strip and Laboratory. The study of the prevalence of HVEB 100% was performed in dairy cows. By the degree of clinical diagnosis it was determined prevalence and 11.46% of the positive samples was obtained. Urinalysis by Reactive (TRU) in this case Tape 15.63% positive samples were obtained and finally Laboratory analysis (EMSU) 10.42% positive samples were obtained being the most effective method to confirm its prevalence. To determine the current status of the area it was conducted surveys to producers which demonstrate the prevalence of hematuria 73.24% with a high incidence of HVEB; Cattle farm types, 98.59% is livestock, livestock production systems, 88.73% extensively, grazing systems handle the 70.42% freely, grazing range 67% have Merkerón (setaria sphacelata), also they perform weed control 62% by manual control, effect of soil conservation practices 7% and finally the producers receive 23.94% of institutional support. It is concluded that the study area is endemic to HVEB.